(untitled) (Global Journal of Management and Business Research, 2013)
This survey uses the sample of total 14 listed firms of related medical industry in the Viet Nam economy and especially, the stock exchange which has been affected by the global crisis during the period 2007-2011. Specifically, we perform the risk re-analysis and estimation for the listed firms in Medicine, Medical equipment and Human resource industries. First of all, using quantitative and analytical methods to estimate asset and equity beta values of three (3) groups of sub-medical listed companies in Viet Nam Medicine, Medical equipment and Human resource industries with a suitable traditional model, we found out that the beta values, in general, for most companies are acceptable, excluding a few cases. There are 57% and 71% of listed firms with lower risk, among total 14 firms, whose beta values lower than () 1 and have stock returns fluctuating more than the market index, indicated by equity and asset beta, accordingly. Ultimately, this paper generates some outcomes that could provides both internal and external investors, financial institutions, companies and government more evidence in establishing their policies in investments and in governance.